Airbnb’s Role In Rural Housing Shortages: A Case Study Of Sussex - Adenegan, Michael Adeyinka; Yusuf, Jamiu Adeniyi (Management Analytics and Social Insights, 2025)
Rural housing affordability has become a critical issue in the United Kingdom, particularly in picturesque and accessible counties like Sussex. This study investigates the extent to which the expansion of the short-term rental platform Airbnb has contributed to housing shortages in the rural parishes of East and West Sussex. Using a panel dataset from 2016 to 2025 at the parish level, this research employs a spatial panel data model to analyse the impact of Airbnb listing density on median house prices, median private rents, and the availability of long-term rental stock. The findings reveal a statistically significant positive relationship between the concentration of entire-home Airbnb listings and escalating housing costs. The conversion of residential properties, including traditional cottages and second homes, into full-time short-term lets is shown to reduce the housing supply available to residents, thereby inflating prices. The Spatial Durbin Model (SDM) confirms the presence of significant spillover effects, indicating that housing market pressures in one parish are transmitted to neighbouring areas. This paper argues that the frictionless nature of the Airbnb platform has intensified pre-existing pressures on rural housing, accelerating a form of "platform-mediated rural gentrification" that displaces local populations and threatens community viability. The study concludes by discussing targeted policy implications, such as the implementation of stricter licensing regimes and the use of planning controls, to mitigate the adverse effects of the short-term rental market and safeguard housing for rural communities.